Mortality trends in Croatia in the first two decades of the 21st century - Vera Graovac Matassi; Adriana Rogić (Geoadria, 2023)
Negative demographic trends in Croatia (natural decrease, negative net migration and population aging) are increasingly influencing socio-economic development of the country. Already in early 21st century, the long term decrease of live births and the increase of deaths were recognized as destabilizing factors of population development in Croatia. After the Croatian accession to the EU, the concerns regarding future demographic development of the country raised even more due to intensive emigration to other EU countries, which coincided with the historically low birth rates and high death rates. The focus of this paper is on mortality trends in Croatia in the first two decades of the 21st century. In this period, mortality in Croatia was influenced by different socio-economic, demographic, and epidemiological factors. Given the lack of recent papers dealing with mortality in Croatia, the main aim of this paper is to provide an overview of the changes in selected mortality indicators and contribute to the discussion on recent mortality trends in Croatia. The results of this research indicate that Croatia experienced some positive changes regarding mortality (increase of life expectancy at birth and decrease of infant mortality rates in the first period, in particular), but, some of the trends are not favourable, particularly the changes in the causes of death. Although improvements were observed regarding the share of deaths caused by the diseases of the circulatory system, there was a notable increase in deaths caused by the endocrine, nutritional and metabolic diseases which can be attributed to the unhealthy lifestyle and various behavioural factors.